HOW SERVANT LEADERSHIP AND EMPLOYEE RELATIONS DRIVE EMPLOYEE ENGAGEMENT: A SEQUENTIAL MEDIATION STUDY IN AN INDONESIAN ENERGY COMPANY - Christianto, Reinardus Dwi Prio; Sukasih, Ahmad Syarifudin; Ali, Muhammad Nur (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the influence of servant leadership and employee relations on employee engagement at PT PLN Indonesia Power UBP Suralaya, with career development and job satisfaction as mediating variables. Using a quantitative causal associative approach, data were collected via questionnaires from 150 employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that servant leadership significantly influences employee engagement both directly (β = 0.342, p < 0.05) and indirectly through career development and job satisfaction. Similarly, employee relations significantly affect Engagement directly (β = 0.285, p < 0.05) and via job satisfaction. Career development and job satisfaction were found to be partial mediators. This research contributes to human resource management theory by offering an integrated mediation model. It provides practical recommendations for improving employee engagement through leadership development, relationship building, and systematic career and satisfaction programs.